This preview shows page 1. Sign up to view the full content.
Unformatted text preview: l a4 = (n*logxy - logx*logy)/(n*logx2 - logx^2) a %a4 = (n*sum(log(x).*log(y)) - sum(log(x))*sum(log(y)))/(n*sum((log(x)).^2) - (sum(log(x)).^2)) ( b4 = ybar - a4*xbar b X = (0.1:.001:2)'; X F = exp(b4 + a4*log(X)); F plot(X, F) p...
View Full Document
This note was uploaded on 09/21/2011 for the course EGM 3344 taught by Professor Raphaelhaftka during the Spring '09 term at University of Florida.
- Spring '09